Qualitätsindikatoren für die Pankreaschirurgie - Wellner, U. F.; Grützmann, Robert; Keck, T.; Nuessler, N.; Witzigmann, H. E.; Buhr, H. -J. (Chirurg, 2018)
Quality indicators are by definition indirect measures of quality. The selection for the field of pancreatic surgery was based on the clinical relevance and controllability, scientific evidence and the practicability of data acquisition. In terms of outcome quality, hospital mortality, the composite endpoint MTL30 (mortality-transfer-length of stay), and major complications (Clavien-Dindo classification grades 3b and 4) were chosen as being essential. With respect to structural quality, the presence of interventional radiology with constant availability was considered essential. To evaluate target values two strategies were used: a systematic literature search and evaluation of the current numbers from the German Society for General and Visceral Surgery (DGAV) StuDoQ|Pancreas registry for the years 2014-2016. The results are presented in the following consensus statement.
EVALuna2:212863